Revealing Tag synthesis pathway in the green microalga Haematococcus pluvialis a source of triacylglycerides for biodiesel and valuable co-products - Scodelaro Bilbao, Paola Gabriela (2017)
Haematococcus pluvialis is an oleaginous microalga known as an important source of the red carotenoid astaxanthin. Recently, we proposed H. pluvialis as a potential source of triacylglycerides (TAG) for biodiesel production, and of phytosterols with potential nutraceutical properties. In this work, our purpose was to study the metabolic pathways involved in TAG synthesis induced by high-light stress in H. pluvialis UTEX 2505. For this end, the strain was grown in Bold’s Basal Medium under high-light intensity or control light for 1, 2 and 3 days. Then, the lipid content and the expression of enzymes known to be involved in lipid metabolism in plants were analyzed. High-light stress significantly stimulated TAG and phytosterol synthesis and accumulation (p<0.01) in all the conditions tested. Red Nile staining analyzed by confocal microscopy confirmed the presence of cytoplasmic lipid droplets after H. pluvialis high-light exposure. The use of propranolol, a lipin inhibitor, significantly diminished (p<0.01) TAG synthesis induced by high-light intensity. Western Blot analysis revealed that high-light stress significantly induced the expression of the fatty acid synthase (FAS) complex (p<0.01), lysophosphatidic acid acyltransferase (LPAAT) (p<0.01) and diacylglycerol acyltransferase (DGAT) (p<0.01) enzymes. In addition, qPCR also showed increased mRNA levels of the above-mentioned enzymes. On the other hand, high-light also induced the expression of the monoacylglyceride (p<0.01) and diacylglyceride (p<0.01) lipases. However, no significant changes (p>0.05) were observed in the release of glycerol to the medium after high-light stress. Together, these results suggest that TAG synthesis in H. pluvialis occurs de novo through stimulation of the fatty acid synthesis pathway and induction of the Kennedy pathway under light stress. Our results constitute the starting point to design molecular strategies for increasing the synthesis of valuable products from H. pluvialis